Proceedings of the 2011 ACM SIGCOMM Conference on Internet Measurement Conference 2011
DOI: 10.1145/2068816.2068825
|View full text |Cite
|
Sign up to set email alerts
|

Sharing graphs using differentially private graph models

Abstract: Continuing success of research on social and computer networks requires open access to realistic measurement datasets. While these datasets can be shared, generally in the form of social or Internet graphs, doing so often risks exposing sensitive user data to the public. Unfortunately, current techniques to improve privacy on graphs only target specific attacks, and have been proven to be vulnerable against powerful de-anonymization attacks.Our work seeks a solution to share meaningful graph datasets while pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
191
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(194 citation statements)
references
References 58 publications
2
191
0
1
Order By: Relevance
“…Grouping has been recently used for differentially-private publication of graph topologies [22,23]. These solutions divide a dataset into disjoint groups, which is different from our interleaved grouping technique.…”
Section: Related Workmentioning
confidence: 99%
“…Grouping has been recently used for differentially-private publication of graph topologies [22,23]. These solutions divide a dataset into disjoint groups, which is different from our interleaved grouping technique.…”
Section: Related Workmentioning
confidence: 99%
“…They found that two models consistently generate synthetic graphs with common graph metric values similar to those of the original graphs, and one produces high fidelity results in application-level tests. In a followup work the authors investigated how to share social network graphs without compromising user privacy [17]. Previous research has also studied how to generate synthetic social graphs with different properties [8], [9].…”
Section: Related Workmentioning
confidence: 99%
“…Third, LBSN datasets with different properties can be generated on demand, which can help researchers improve the statistical confidence in their experimental results. Previous work investigated the graph models that produce synthetic social graphs of online social networks [8], [9], [16], [17]. Given all these advantages of the model-generated LBSN datasets, however, no LBSN model has been proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Happily, the answer is no. The analysis of [13] shows that the noise required to protect the privacy of the JDD can be non-uniform: for each (d1, d2) entry of the JDD, it suffices to add noise proportional to 4 max(d1, d2). Indeed, one consequence of our work is that these sorts of non-uniformities exist in many graph analysis problems, e.g., counting triangles, motifs, etc..…”
Section: Exploiting Non-uniform Noisementioning
confidence: 99%
“…We can significantly improve the accuracy of differentially private graph measurements by exploiting opportunities to apply noise non-uniformly [13]. However, each new measurement algorithm requires a new non-trivial privacy analysis, that can be quite subtle and error prone.…”
Section: Without Custom Technical Analyses!mentioning
confidence: 99%